2020
DOI: 10.3389/fchem.2020.00715
|View full text |Cite
|
Sign up to set email alerts
|

High Power Energy Storage via Electrochemically Expanded and Hydrated Manganese-Rich Oxides

Abstract: Understanding the materials design features that lead to high power electrochemical energy storage is important for applications from electric vehicles to smart grids. Electrochemical capacitors offer a highly attractive solution for these applications, with energy and power densities between those of batteries and dielectric capacitors. To date, the most common approach to increase the capacitance of electrochemical capacitor materials is to increase their surface area by nanostructuring. However, nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…62 The water within the interlayer can improve cation transfer from the bulk electrolyte to the particles. 64 The band gap was tested by recording the absorption spectra of the solid materials. No obvious differences can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…62 The water within the interlayer can improve cation transfer from the bulk electrolyte to the particles. 64 The band gap was tested by recording the absorption spectra of the solid materials. No obvious differences can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive efforts have been put forward to enhance the specific surface area of electrochemical capacitor materials using nanostructuring in order to increase their capacitance. Still, lower volumetric capacitance is one of the major downsides of nanostructured materials [86]. Amorphous MnO 2 compounds were surveyed as plausible materials for serving as electrodes for electrochemical capacitors in 0.1 M K 2 SO 4 electrolyte by Brousse et al and they found a large capacitance value.…”
Section: Energy Storagementioning
confidence: 99%
“…Extensive efforts have been put forward to enhance the specific surface area of electrochemical capacitor materials using nano‐structuring in order to increase their capacitance. Still, lower volumetric capacitance is one of the major downsides of nanostructured materials 86.…”
Section: Applications Of Manganese Oxide Nanomaterialsmentioning
confidence: 99%
“…The electrode materials for pseudocapacitors mainly include metal oxides and conductive polymers [13,14]. Pseudocapacitors store energy through reversible reactions on the surface of the electrode, demonstrating a mechanism that is more intricate than that of EDLCs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%